PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT MANGGALA RADHIKA ABIYASA CIRUAS KABUPATEN SERANG - Salapudin, Salapudin; Lesmana, Ihwan Satria (Gapenas Publisher, 2025)
The research problem in this study is whether recruitment and training affect employee performance, either partially or simultaneously. This study aims to analyze and prove the influence of these two variables on improving employee performance at PT. Manggala Radhika Abiyasa. The method used is a quantitative approach with a survey technique involving 70 respondents. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination with the help of SPSS version 27. The results show that recruitment has a significant effect on performance with a t-value of 4.146 and a significance value of 0.000. Training also has a significant effect, with a t-value of 3.470 and a significance value of 0.001. Simultaneously, recruitment and training have a significant effect on performance, with an F-value of 76.894 and a significance value of 0.000. The coefficient of determination (R²) value of 0.697 indicates that 69.7% of the variation in performance is explained by these two variables. In conclusion, the improvement of security personnel performance is strongly influenced by the effectiveness of recruitment and training. Therefore, the integration of selection and development strategies is necessary to produce professional and job-ready security personnel.